(untitled) (FUDMA JOURNAL OF SCIENCES, 2023)
In this study, Response Surface Methodology (RSM) was applied to the analysis of ozone and Sulphur dioxide on soybean. The data used was secondary data which came from research on the effects of air pollutants on crop yields conducted in North Carolina State University and USDA in 1981. From the analyses, the adequacy of the model used was validated with the F-value of 18.71 and 18.55 respectively suggests the models are significant. The Coefficient of Determination the Adjusted ,written as and Predicted were also used to find the adequacy of the model used. Effects of ozone and Sulphur dioxide were looked into in the yields of soybean in two different locations. It was found that the 0.395 inlet of sulphur and 0.018 inlet of ozone gives optimum yield of 724.427 grams of soybeans in yield 1 and same quatity gives optimum yield of 248.282 grams of soybeans in yield 2 which made ozone and sulphurdioxide to have significant effect on the yield of soyabeans.